Meat production and consumption: an ethical educational approach - Brügger, P.; Marinova, Dora; Raphaely, T. (2016)
This chapter presents the results of studies that unveil how meat and other animal derived products are causing severe environmental impacts, social problems and ethical concerns regarding both human and non-human animals. Although there are many ways to tackle the issue a critical non-anthropocentric education that encompasses ethics as a dimension of sustainability, is proposed. Traditional non environ-mental education often legitimizes values that are averse to an ethic that could be described as correct regarding the relationship between humans and the other animal species and even many educational currents that call themselves “environmental” are guided by a shallow conservationist point of view. Although welfarist practices may in some contexts be of help, the authors propose the animal abolitionist perspective as the unique genuine foundation for education to build this new paradigm.